Performance analysis of full‐duplex device‐to‐device transmitter aided non‐orthogonal multiple access - Lijun Bai; Li Hao; Ke jun Jia (IET Communications, 2022)
Abstract In this paper, a three‐user non‐orthogonal multiple access (NOMA) system based on device‐to‐device (D2D) communication and full‐duplex (FD) transmission is proposed, in which the D2D user acts as a decode‐and‐forward (DF) relay to forward the signal from the base station (BS) to the far user, forming a system termed the FD D2D transmitter aided NOMA (FD‐D2D‐NOMA). In practical NOMA systems, due to the limitation of decoding ability, the near user cannot always perform successive interference cancellation (SIC) successfully. By considering perfect SIC (pSIC) and imperfect SIC (ipSIC), the close‐form expressions for the ergodic sum capacity and outage probability of the proposed FD‐D2D‐NOMA scheme are derived, which match well with the simulation ones. The ergotic sum capacity and outage probability under different levels of residual self‐interference at the FD user and residual interference at the far/near user due to ipSIC are investigated, and the results show that, such interferences have significant impact on the performance of the proposed scheme. Moreover, the analytical and simulation results illustrate the performance gain of the proposed scheme compared with other ones under both pSIC and ipSIC scenarios. The impacts on performance exerted by channel conditions and design parameters are also discussed in this paper.